Magmatic Triggering of Earthquakes on Distal Faults as a Potential Medium‐Term Warning Signal From Ruapehu Volcano - Tony Hurst; Geoff Kilgour; Ian Hamling (Geophysical Research Letters)
Abstract A major eruption sequence of Ruapehu volcano began on 17 September 1995, with only hours of local precursory seismicity. However, from about 10 to 5 months prior to the eruption, an unusually high number of tectonic earthquakes occurred between 15 and 20 km west of Ruapehu. Diffusion chronometry of zoned crystals within erupted scoria from the 1995 eruptions of Ruapehu provide a petrological timescale of magmatic processes before the eruption. This timescale coincides with the seismicity to the west of Ruapehu. Stress modeling shows that stress changes due to movement of newly mixed magma from a sill under Ruapehu would have significantly added to the stress on preexisting faults, thereby providing a mechanism to explain the observed pre‐eruption seismicity. This shows that tectonic earthquakes in the vicinity of an active volcano may be an indication of magma movement and should be viewed as a possible eruption precursor.